Ciência Aberta em universidades públicas federais brasileiras: políticas, ações e iniciativas - Nivaldo Calixto Ribeiro (2022)
Scientific research, in its great majority, is conducted in public universities, many of them financed in part or in whole with public resources. Considering that society has the right to a refund of its investments, these universities have the responsibility to promote a more open science. In this scenario, the question is: How are Brazilian federal public universities developing Open Science strategies? Therefore, this research aims to analyze how these universities are acting to promote and adhere to the Open Science movement. Specific objectives are: reflect on Open Science, observing conceptual structures of its representation and its interpretative currents, in order to build the units and sub-units of analysis of this research; discuss public universities and their role in the development of research in Brazil; evidence actions and initiatives of Brazilian federal public universities focused on Open Science; develop a web application to evaluate the adherence to Open Science by Brazilian federal public universities present the proposal for the creation of an Open Science Agency, with the purpose of giving support to federal universities on the subject and present how was the implementation and the way of acting of the scientific dissemination channel Ciência da Informação Express - CIExpress. The technical procedures adopted were a bibliographic survey, document analysis, complemented by the application of a questionnaire, and a multi-case study, analyzing the adherence to Open Science in seven universities. According to the results obtained, it was possible to identify that universities have been developing Open Science actions and practices, although it still requires governmental legislation for its consolidation. Six analysis units were created: Open Access, Open Research Data, Open Science Evaluation, Open Science Infrastructure, Open Reproducible Research and Citizen Science, subdivided into 20 sub-units. Based on the results obtained, it was possible to identify how universities have developed Open Science actions and practices, although it still needs government legislation for its consolidation. The Academic Technology Center, the Institutional Strategic Data Office, the Innovation Shelf, and the Laboratory of the Future were revealed as innovative actions of universities and three products of this research were presented: an Open Science Agency, a web application for self-assessment of adherence to Open Science and the scientific dissemination channel Information Science Express. As final remarks, it is understood that Open Science is a complex and broad movement, composed of recommendations for a new modus operandi of science. It was not the intention of this research to address all the dimensions, boundaries and specificities of the movement. However, it was developed a set of units that may involve a satisfactory part of the whole, discussed in the literature, registered in institutional and governmental policies and guidelines, which can be used as a guide for those institutions that are looking for directions to adhere to Open Science.